THE EVOLUTION OF CORPORA - Turobova, G; Fayzieva, M. Ch (Innovative Development in Educational Activities, 2023)
The article reveals common corpus secrets and types. It gives some data about COCA, common corpus, sublanguage corpora, and the Oxford English Corpus. One of the most rapidly expanding approaches in modern linguistics is corpus linguistics. In the field of applied linguistics, large collections of written and spoken texts that have been specifically chosen to reflect certain linguistic contexts, such as casual conversation or academic writing, are analyzed.